Crosslinking bacterial postbiotics for microbial and quality control of strawberries postharvest: bacteriological and 16S amplicon metagenome evidence - Tenea, Gabriela N.; Reyes, Pamela; Flores, Carlos (Frontiers in Microbiology, 2025)
IntroductionStrawberries are renowned for their exceptional flavor and nutritional properties but have a short shelf life due to rapid ripening and a high vulnerability to postharvest microbial decay. Postbiotic formulations (PBFs) derived from lactic acid bacteria (LAB) can be developed into effective preservation products, extending postharvest shelf life while maintaining fruit quality.MethodsThis study aimed to assess the effects of postbiotic-based formulations (PBFs) consisting of two key components: (1) a precipitated peptide-protein extract (PP) from Weissella cibaria UTNGt21O, serving as the antimicrobial agent, and (2) an exopolysaccharide (EPS) from W. confusa UTNCys2-2, functioning as the biopolymer carrier. These formulations were tested against a multidrug-resistant Serratia liquefaciens P4StpC1 strain, isolated from ready-to-eat strawberries, and their potential mode of action was analyzed in vitro. Time-kill assays and electron microscopy were used to evaluate their impact on the target cells. Furthermore, the performance of PBFs was compared to a commercial disinfectant (C1) in terms of their effects on strawberry microbiota and fruit quality, employing bacteriological techniques and 16S amplicon metagenomic analysis.ResultsThe selected PBFs showed bacteriolytic effect on Serratia in vitro. The target cell viability was significantly reduced upon 1 h co-cultivation by inducing several morphological and ultrastructural modifications. Dipping strawberries at the ripe stage four in PBFs indicated no increase in total cell counts, thus the microorganisms colonization was retained during storage with refrigeration. The 16S metagenome analysis showed that the treatment impacted the fruit microbiota, significantly increasing Lactobacillus abundance (p < 0.001) by day eight compared to the disinfectant control. This suggests the formulation supports beneficial microbes, enhancing antimicrobial effects. Additionally, the postbiotic coating improved shelf-life, preserved fruit quality, and delayed deterioration in strawberries. The strawberries quality attributes were not affected by the treatment. Principal Component Analysis (PCA) revealed clear sample separation based on maturity stage, independent of the treatment.ConclusionThe results highlight the potential of crosslinking of a peptide-protein fraction with EPS to prevent the colonization of undesirable microorganisms on postharvest strawberries while enhancing their safety and quality.